Exploring the effects of social responsibility on coordination and profit division in a supply chain. (15th December 2016) - Panda, S.; Modak, N.M.
Abstract: This paper explores channel coordination and profit division in a socially responsible manufacturer-retailer chain through sub-game perfect equilibrium and extended alternative offer bargaining. The channel members jointly intend to swell stakeholder's welfare by exhibiting corporate social responsibility (CSR) in a proportion. It is found that (i) the channel's non-profit maximizing motive through CSR practice generates higher profit margin than would the profit maximizing objective, (ii) the manufacturer's wholesale price is below its marginal cost or negative above some thresholds of CSR and CSR sharing fraction, (iii) the CSR and CSR sharing fractions are key determining factors for the pure profits of the channel members because variations in choosing these two factors can lead to increment or decrement, even negative pure profits. On the other hand, for the CSR manufacturer, the wholesale price is less than the marginal cost for CSR practice above a threshold and is negative for heavy CSR practice though always larger than the marginal cost for the CSR retailer. So, the manufacturer's pure profit may be negative. Moreover, a channel member always prefers the other's CSR practice. Thus, in cooperative environment, equitable share of CSR may be a compromise solution. Graphical abstract: Highlights: Strategic bargaining is used for coordination and profit division in a supply chain. Non-profit maximizing firm may earn higher profit than would profit-maximizer. Wholesale price is less than marginal cost or negative for heavy CSR practice. Variations in choosing CSR and CSR sharing fraction can lead to negative pure profits. A channel member prefers other's CSR. So equitable surplus share may be a compromise solution.